Seed Yield and its Components in Winter Regenerated Flush of Buffel Grass (Cenchrus ciliaris Linn.) under Rainfed Conditions of Rajasthan - M.P. RAJORA; MANJIT SINGH (Seed Research, 2026)
Thirteen accessions of Cenchrus ciliaris were evaluated for seed yield and its components in a completely randomized block design under rainfed conditions. The extent of variability was high for all the traits studied. Estimates of heritability and genetic advance were also high. Highest seed yield (381.8 kg/ha) was recorded in accession CAZRI 2162 from winter-regenerated flush after taking herbage yield during November 2001. It was closely followed by CAZRI 1106 (346.5 kg/ha). The yield of these accessions was significantly higher than var. CAZRI 75 (172.2 kg/ha). The high mean seed germination (45.7%) indicated the good quality of seed. The number of spikes per plant had positive and significant association with seed yield (r= 0.76). Number of spikes per plant and seed yield had more variability among accessions and showed high heritability and genetic advance implying that winter seed yield can be improved by simple selection. The study demonstrates the potential for quality seed production of buffel grass during winter in dry areas of western Rajasthan. The study was undertaken from June 2001 to September 2002.